2011
DOI: 10.1002/cb.374
|View full text |Cite
|
Sign up to set email alerts
|

Help me, I'm fat! Social support in online weight loss networks

Abstract: Social networks have become an increasingly common way for people to share information and seek emotional support for issues surrounding weight loss. This study aims to explore how users of a commercial social networking site who are focussed on weight loss give and/or receive social support to/from other users. The authors use quantitative data from 145 members of the Weight Watchers Facebook page to explore how social support is both given and received, and the communication style by which this is achieved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 21 publications
8
123
1
5
Order By: Relevance
“…First, the results enrich the discussion about functional social support types in the online environment and their dependence on the delivery platform. The study results confirm the findings that OSGs in Facebook [1,35] and in online forums [16][17][18] can provide a venue for their members to give and receive social support, particularly emotional and informational support. The study results also show that instrumental support can be shared through the online environment, in contrast to the findings of Hwang et al [18].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…First, the results enrich the discussion about functional social support types in the online environment and their dependence on the delivery platform. The study results confirm the findings that OSGs in Facebook [1,35] and in online forums [16][17][18] can provide a venue for their members to give and receive social support, particularly emotional and informational support. The study results also show that instrumental support can be shared through the online environment, in contrast to the findings of Hwang et al [18].…”
Section: Discussionsupporting
confidence: 85%
“…Through the use of social networking site (Facebook), the young adults were able to expand their food choices by finding new inspirations for cooking and were encouraged by social media to make positive food choices. A study inspecting Weight Watchers' Facebook page concluded that the Facebook community could provide a venue for its members to give and/or receive emotional and informational support [1]. Based on this and the discussion in Section 2.1, we suggest the following hypotheses: Although emotional and informational support can be found in both kinds of platforms, there is some evidence that these channels differ in the functional support types that they primarily provide.…”
Section: H2: Increased Frequency Of Using Online Forum Based Peer Supmentioning
confidence: 87%
See 1 more Smart Citation
“…These two dimensions shape online social support. Social interactions of consumers through social media generate both emotional and informational support (Ballantine & Stephenson, 2011). Emotional and informational support are the two main dimensions of social support in an online context (Hajli, 2014b).…”
Section: Social Supportmentioning
confidence: 99%
“…Social media allows marketers to build a public vote, website presence and strengthen other communications. By using social media, consumers can create content, offer valuable advice to others, exchange information, and generate social support [5][6] [7] [8].…”
Section: Literature Reviewmentioning
confidence: 99%